Comparison of the Treatment Outcome of Oral Tofacitinib with Other Conventional Therapies in Refractory Alopecia Totalis and Universalis: A Retrospective Study - Jung-Won Shin; Chang-Hun Huh; Min-Woo Kim; Ji-Su Lee; Ohsang Kwon; Soyun Cho; Hyun-sun Park (Medical Journals Sweden, 2018)
Treatment of alopecia totalis and alopecia universalis is often challenging and unsatisfactory. Recently, Janus kinase inhibitor has shown promising results. The aim of this study is to compare the efficacy and tolerability of oral tofacitinib and conventional modalities for treating refractory alopecia totalis/universalis. A total of 74 patients (18 treated with tofacitinib, 26 treated with conventional oral treatment (steroid ± cyclosporine), and 30 treated with diphenylcyclopropenone) were included in the study. The patients' medical records were reviewed retrospectively. After 6 months, 44.4% of patients in the tofacitinib group, 37.5% in the conventional oral treatment group, and 11.1% in the diphenylcyclopropenone group achieved 50% improvements in the Severity of Alopecia Tool score. During treatment, 10% of patients in the tofacitinib group, 73.1% in the conventional oral treatment group, and 10% in the diphenylcyclopropenone group experienced adverse drug reactions. In conclusion, oral tofacitinib was more effective than diphenylcyclopropenone immunotherapy and more tolerable than conventional oral treatment after 6 months of treatment.